An Introduction to Computer Programming Using the BASIC Language. - Nugent, Christopher E.; Bruns, William J. (The Accounting Review, 1968)
Reviews the book "BASIC: An Introduction to Computer Programming Using the BASIC Language," by William F. Sharp.